Power quality improvement using unified power quality conditioner - Tey, Leong Hua (2008)
In this thesis, the applications of Artificial Neural Network (ANN) techniques as controllers for the shunt active filter and Unified Power Quality Conditioner (UPQC) are proposed. The research in this thesis includes building up the conventional shunt active filter and UPQC from scratch using analogue electronic components. The design concept of the analogue shunt active filter is used to build a digital signal processing (DSP)-based shunt active filter.